Distal Biceps Repair: 2-Volar Incision Technique for Acute and Chronic Retracted Tears - Suvleen K. Singh BS; J. Mattison Pike BS; Grace Bennfors BS; Megan E. Welsh BS; Richard J. Friedman MD, FRCSC; Josef K. Eichinger MD (SAGE Publishing, 2022)
Background: A distal biceps repair is performed after a rupture of the distal biceps tendon, an injury that typically affects the dominant arm of middle-aged men, resulting in weakness in supination and elbow flexion. A volar 2-incision technique minimizes skin incision length while optimizing exposure to anatomical structures through proper incision placement for acute repair and chronic reconstruction with graft. Indications: Retraction of the distal biceps away from its insertion on the proximal radius in the chronic setting can require a more extensile incision. Two transverse incisions are strategically placed on either side of the antecubital fossa to optimize exposure of the radial insertion site and proximally to retrieve the retracted tendon for either acute or chronic retracted distal biceps tears with or without graft reconstruction. Technique Description: A transverse incision is made in the forearm directly over the radial tuberosity. This facilitates direct exposure and drilling of a socket for placement of the distal biceps' tendon with suture button and interference screw construct. A second proximal transverse incision is made to identify and retrieve the retracted tendon. The tendon is retrieved and prepared or reconstructed with graft for chronic cases with suture. The tendon and graft are tunneled under the skin bridge between the 2 incisions. The sutures are then loaded onto a titanium button, which is deployed onto the far cortex. The tendon is advanced into the tunnel, an interference screw is placed, and the sutures are tied. Results: Restoration of anatomy and correct placement of the 2 incisions is facilitated with this approach, restoring distal biceps function without requiring extensile volar exposure of the entirety of the length of the distal biceps tendon. Discussion/Conclusion: This technique mitigates the need for extensive dissection. It also facilitates improved visualization of relevant structures for cases with substantial tendon retraction, even in the case of chronic retracted tears requiring allograft reconstruction. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.